An audit of HIV testing practice in people aged 50 years and over presenting with a known clinical indicator condition in secondary care. Issue 2 (10th July 2022) - Gill, Rebecca Catherine; Levett, Tom; Youssef, Elaney
Abstract: Objectives: To evaluate HIV testing of patients aged ≥50 years presenting to secondary care with clinical indicator conditions (CICs) for HIV. Methods: Retrospective audit of electronic records for patients aged ≥50 years discharged from hospital between January 1st and July 31st 2019 who had at least one documented CIC. Patient demographics and HIV testing data were collected from clinical systems (excluding sexual health databases). Results: 2478 patients with a CIC were identified. 222 (9.0%) received an HIV test within 31 days of discharge. Patients receiving a test were significantly younger (mean 68.6 versus 75.3 years; P < 0.001) and significantly more men underwent testing than women (60.4% versus 39.6%; P = 0.001). 32 CICs were identified across nine disease systems. By system, those with a haematological CIC were significantly more likely to undergo testing compared with all other CICs combined (P < 0.001). Of individual CICs, patients with Kaposi's sarcoma, hepatitis C, neutropenia, lymphadenopathy, pyrexia of unknown origin and thrombocytopenia (P < 0.001), and seborrhoeic dermatitis, hepatitis B, other unexplained blood dyscrasia, and non‐Hodgkin's lymphoma (P < 0.05) were more likely to undergo testing than those presenting with other CICs. Patients with dementia and lung cancer were less likely to undergo testing (P < 0.001). Patients presenting with a greater number of CICs were significantly more likely to undergo testing (P = 0.002). Conclusions: HIV testing among patients aged ≥50 years presenting to secondary care with a CIC is low. Work is needed to improve HIV testing practice in this patient group.